Negara Asal Produk, Persepsi Kualitas dan Merek: Pengaruhnya terhadap Keputusan Pembelian Smartphone - Mahardika Ardaka Saputra; Ade Octavia; Suswita Roza; Yayuk Sriayudha (Universitas Samudra, 2019)
This study aims to examine the effect of country of origin, perceived quality and brand on smartphone purchasing decisions. The subject of this study is a smartphone that is sold officially in Indonesian market. The sampling technique used was purposive sampling with the number of samples used amounting to 120 samples which were active users of smartphones. Validity and reliability test results show that the research instrumentsare valid and reliable. The analysis technique used is multiple linear regression analysis using SPSS version 22 software. The results show that country of origin variables partially do not have a positive and significant effect on purchasing decisions while perceived quality and brand variablespartially positive and significant influence purchasing decisions. Simultaneously, country of origin variables, perceived quality and brand have a positive and significant effect on purchasing decisions.